Literasi Informasi Gizi Pada Masyarakat Usia Produktif di Kota Semarang, Indonesia: Nutrition Fact Literacy in Productive Age Communities in Semarang City, Indonesia - Aprianti Aprianti; Kismi Mubarokah; MG Catur Yuantari; Nis Syifa’ur Rahma (Amerta Nutrition, 2023)
Background: Lack of attention to reading nutritional value information labels on packaged food can harm one's health, such as an increased risk of obesity and degenerative diseases. The results of a study by the National Consumer Protection Agency stated that only 6.7% of consumers in Indonesia paid attention to nutritional value information labels. Objectives: This study aims to determine the relationship between demographic characteristics and nutritional value information literacy. Methods: This quantitative study with a cross-sectional design was conducted on Semarang City residents aged 15-65. The sample size used the Slovin formula so that a minimum sample size of 1,029 respondents was selected using multistage random sampling based on characteristics of educational level and social status. The relationship between nutrition fact literacy and demographic characteristics was used using the Chi-square statistical test, and the relationship between nutrition fact literacy and body mass index using the Spearman rank statistical test. Results: The study showed that nutrition fact literacy was still problematic, 96.1%. Respondents have normal nutritional status, as much as 64.1%. Factors related to nutrition fact literacies were educational level (p=0.039, OR=1.968) and occupation (p=0.002, OR=4.668). Demographic variables unrelated are domicile, gender, marital status, and residence status. There is no relationship between nutrition fact literacy and nutritional status. Conclusions: Respondents with low nutritional value information literacy live in rural areas, are married, live with their families, have a low level of education, and do work, not in the health sector.